A Review of Potential Method for Optimization of Power Plant Expansion Planning in Jawa-Madura-Bali Electricity System - Setya Budi, Rizki Firmansyah; Sarjiya, Sarjiya; Hadi, Sasongko Pramono (Communications in Science and Technology, 2017)
The paper contains a literature review to obtain an optimization method that potentially can be used to optimize power plant expansion of Jawa-Madura-Bali (Jamali) power system in 2015-2050. An optimization model that can represent auction process and direct appointment of IPP by considering the long term period (multi-period framework) and multi-objective function (economical, reliable, and environmentally friendly), is needed. Based on the literature review that has been done, it is obtained the method that potentially can be used for the Jamali optimization is game theory with multi-period, bi-level and multi objective optimization method. Game theory is used to represent the auction process and direct appointment of IPP. Multi-period is used to represent the long term period from 2015-2050. Multi-objective optimization method is used to represent the aspects of cost, reliability, and CO2 emission which are considered in the optimization process